Restructuring the Austrian Energy System: An Extended Technology Wedges Approach - Claudia Kettner; Daniela Kletzan-Slamanig; Angela Köppl; Stefan Schleicher; Andrea Damm; Karl W. Steininger; Brigitte Wolkinger; Hans Schnitzer; Michaela Titz; Heidemarie Artner; Andreas Karner (Austrian Institute of Economic Research (WIFO), 2011)
EU climate and energy policy defines ambitious objectives for the EU member countries requiring a fundamental change of energy systems. This paper suggests basing the analysis of restructuring options on energy services instead of energy flows. In order to provide the energy services in a sustainable way the guidelines "low energy - low carbon - low distance" should be used. This refers to an increase in energy efficiency, the reduction of fossil fuels and the reduction of (redundant) transport. An extended technology wedges approach is applied for Austria to illustrate emission reduction options through technological and behavioural changes. Two portfolios of technology wedges are quantified regarding their effects on energy flows and emissions as well as the economic impacts of investments required.
Keywords: 330; climate and energy policy; energy services; technology options; input-output analysis; Energieversorgung; Energiekonsum; Energiepolitik; Technischer Fortschritt; Energieeinsparung; Input-Output-Analyse; Österreich